Using Library activities to develop teaching-learning French at Faculty of Education at the Francophone Center, National University of Lao: https://doi.org/10.69692/SUJMRD090112 - THAMMASALO, Olady; BOUNCHALEUNH, Laongdao; DYVANHNA, Sènglamphan; DORBOUNGNOU, Thanwaphone; DEROBERT, Olivia (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research report combines two objectives 1). to study additional activities outside the classroom to improve the learning of French in the first year of the French license at the Department of Foreign Languages, Faculty of Education National University of Lao, and 2). to study the satisfaction of the students with the activities. In addition, these activities are intended to allow students to usefully occupy their free time and to promote the practice of language skills and group work. The target group of the research is students from 1st to 3rd year, with a total of 40 people, 28 women. They have an intermediate level of French and they all need to participate in the activity. The research tool was a questionnaire based on the 5-level Likert rating scale. The statistics used to describe the search results are frequency, percentage, and average. The activities in which most students participate with interest are “talking with French people” and “searching for documents,” so the research group can say that both activities are very interesting (F = 97.5% and F = 100%). The research group can therefore say that both activities are very interesting (F = 97.5% and F = 100%). In addition, the research group found that the level of satisfaction is very high in terms of reading French books (58%), in terms of watching films French 67%, in terms of conversation with French speakers (52.5%), in terms of listening to French music 50%, in terms of computer learning (50%) and in terms of finding passages (50%). Furthermore, students develop and strengthen their knowledge of France. Students can also practice communication and have the courage to express themselves in French. Therefore, teachers must also teach French culture because it is very necessary that students know well. Thus, the research group can conclude that these activities outside the classroom contribute to stimulating students' desire to learn French. The various activities were achievement for the goal setting due to the activities management was increased students’ interest in learning French while teachers’ teaching.